CLIMATE CHANGES - CHALLENGES AND POSSIBLE SOLUTIONS (Heritage, 2022)
Climate changes are a topic which has been gaining attention of the global scientific and professional public increasingly for years. The question that has been on the agenda of conferences addessing this issue is how much time has left for us and whether a human can emerge as the winner in the struggle against climate changes bearing in mind that nature will always find a way to confront its uncontrolled destruction. With their activities, above all by uncontrolled technological progress (development), humans brought the Earth into the current state. A wish to earn as much profit as possible neglected the fact that economic interest and interest related to the environment can be balanced only by sustainable development. This is why this century will be to a great extent defined by a manner how we deal with climate changes. Since, “effort is pointless if nature confronts”, Lucius Annaeus Seneca.
Keywords: climate change, sustainable development, Oslo Principles, UN Climate Change Conference in Katowice, UN Climate Change Conference in Madrid